Vaginal applying of 17β-estradiol in the treatment of urogynecological complaints – own experiences - Surkont, Grzegorz; Suzin, Jacek; Wlaźlak, Edyta; Paszkowski, Tomasz; Rechberger, Tomasz (Menopause Review/Przegląd Menopauzalny, 2005)
92 women (aged 45-77 yrs) with urogenital complaints (atrophic vaginitis, dyspareunia and/or urinary incontinence) were recruited to take part in this prospective study. We analyzed the tolerabilty profile, compliance, patient’s satisfaction and the efficacy variables during the three months of treatment with vaginal tablets containing 25 µg of 17β-estradiol (Vagifem, Novo Nordisk). Clinical evaluation and the questionnaire study were performed at the baseline and after 6 and 12 weeks of the treatment. Eighty three women (90.2%) who fulfilled the last visit served as a study population. Treatment with vaginal tablets containing 25 µg of 17β-estradiol appeared to be effective in reducing atrophic vaginitis symptoms in postmenopausal women. A significant reduction of subjective symptoms of urinary incontinence was observed by 21.7% of patients. Vaginal tablets with ultra-low dose of estradiol have good tolerability profile and are associated with high degree of compliance.